Early intervention in Portugal: family support and benefits - Leite, Carina Sofia Correia (2013)
This study investigated the support and benefits of early intervention (EI) in families with children with special needs. Data were gathered through a written questionnaire, ‘Family Benefits Inventory’, completed by 126 families with children with special needs supported by EI teams, with ages from six months to six years in Portugal. The global results obtained in this study allowed us to conclude that families considered that they obtained benefit from EI and received support most of the time in the different dimensions of the questionnaire. Furthermore, support given by an EI professional had a positive influence on families’ perceptions regarding the benefits of EI.